Fire structural performance of thermo-mechanically compressed spruce timber by means experiments and a three-step multi-reactions pyrolysis 3D-finite element modelling. (21st February 2022) - Tran, T.T.; Thi, V.-D.; Oudjene, M.; Khelifa, M.; Girods, P.; Debal, M.; Rogaume, Y.; Jannot, Y.
Highlights: Thermal properties of compressed and uncompressed wood have been assessed. Kinetic parameters governing the pyrolysis of compressed and uncompressed wood have been assessed by means a TGA. A multi-reactions steps pyrolysis FE-model has been developed and validated. The behavior of compressed and uncompressed wood samples exposed to fire have been assessed via a cone calorimeter. Abstract: This paper presents experimental and numerical investigations to access the relative fire structural resistance of thermo-mechanically compressed (or densified) spruce wood. First of all, thermal characterization, including thermal conductivity and specific heat, has been undertaken on both compressed and uncompressed spruce wood. The thermal degradation of both compressed and uncompressed wood has been analysed by means thermogravimetric tests using different heating rates. Both compressed and uncompressed spruce samples of dimensions of 100 mm × 100 mm × 19 mm have been subjected to fire in a cone calorimeter under 20 kW/m 2 and 75 kW/m 2 . Finally, a predictive finite element model based on three-step multi-reactions of pyrolysis is proposed for the thermal transfer and degradation analyses of timber material. The simulated thermal profiles, the mass loss as well as the charring depths were compared to the experimentally recorded results showing a fairly good agreement.